2023
DOI: 10.3389/fimmu.2023.1130933
|View full text |Cite
|
Sign up to set email alerts
|

ILC2 require cell-intrinsic ST2 signals to promote type 2 immune responses

Abstract: The initiation of type 2 immune responses at mucosal barriers is regulated by rapidly secreted cytokines called alarmins. The alarmins IL-33, IL-25 and TSLP are mainly secreted by stromal and epithelial cells in tissues and were linked to chronic inflammatory diseases, such as allergic lung inflammation, or to resistance against worm infections. Receptors for alarmins are expressed by a variety of immune cells, including group 2 innate lymphoid cells (ILC2s), an early source of the type 2 cytokines, such as IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 48 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Measurements of cytokines associated with a type 2 immune response demonstrated higher levels of IL-13 and IL-4 in the COVID-19-positive group compared to the negative group. We also observed higher levels of the alarmin cytokines IL-33 and IL-25 in COVID-19-positive patients, which could be driving type 2 inflammation through polarization of T helper cells or activation of ILC2 [ 46 ]. Paula et al reported higher IL-4 levels and correlated tissue damage resulting from the heightened type 2 response.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of cytokines associated with a type 2 immune response demonstrated higher levels of IL-13 and IL-4 in the COVID-19-positive group compared to the negative group. We also observed higher levels of the alarmin cytokines IL-33 and IL-25 in COVID-19-positive patients, which could be driving type 2 inflammation through polarization of T helper cells or activation of ILC2 [ 46 ]. Paula et al reported higher IL-4 levels and correlated tissue damage resulting from the heightened type 2 response.…”
Section: Discussionmentioning
confidence: 99%
“…TSLP (thymic stromal lymphopoietin), interleukin 33 (IL33) and interleukin 25 (IL25) are three typical epithelial cytokines that contribute to epithelial homeostasis and alert the immune system to external insults in order to regulate tissue restoration and repair ( Ham et al, 2022 ; Mahapatro et al 2021 ; Roan et al 2019 ). These three “alarmin” cytokines are specifically potent in activating type 2 innate lymphoid cells (ILC2s) and therefore their roles have been widely studied in allergic inflammation and exacerbations, as well as parasite infections in the gut ( Hammad and Lambrecht, 2015 ; Topczewska et al, 2023 ). Amplification or intensification of their secretion signals lead to different inflammatory diseases that we have tried to summarise in Table 2 .…”
Section: The Mucus and The Secretome: Let’s Keep It Wet And Clean!mentioning
confidence: 99%
“…TSLP (thymic stromal lymphopoietin), interleukin 33 (IL33) and interleukin 25 (IL25) are three epithelial cytokines that contribute to epithelial homeostasis and alert the immune system to external insults in order to regulate tissue restoration and repair (Ham et al, 2022;Mahapatro et al 2021;Roan et al 2019). These three "alarmin" cytokines are specifically potent in activating type 2 innate lymphoid cells (ILC2s) and therefore their roles have been widely studied in allergic inflammation and exacerbations, as well as parasite infections in the gut (Hammad and Lambrecht, 2015;Topczewska et al, 2023). Amplification or intensification of their secretion signals lead to different inflammatory diseases that we have tried to summarise in Table 2.…”
Section: Cytokinesmentioning
confidence: 99%